Risk Management and Adaptation for Extremes and Abrupt Changes in Climate and Oceans: Current Knowledge Gaps - Bouwer, Laurens M.; Cheong, So-Min; Jacot Des Combes, Hélène; Frölicher, Thomas L.; McInnes, Kathleen L.; Ratter, Beate M. W.; Rivera-Arriaga, Evelia (Frontiers in Climate, 2022)
Perspectives for risk management and adaptation have received ample attention in the recent IPCC Special Report on Changes in the Oceans and Cryosphere (SROCC). However, several knowledge gaps on the impacts of abrupt changes, cascading effects and compound extreme climatic events have been identified, and need further research. We focus on specific climate change risks identified in the SROCC report, namely: changes in tropical and extratropical cyclones; marine heatwaves; extreme ENSO events; and abrupt changes in the Atlantic Meridional Overturning Circulation. Several of the socioeconomic impacts from these events are not yet well-understood, and the literature is also sparse on specific recommendations for integrated risk management and adaptation options to reduce such risks. Also, past research has mostly focussed on concepts that have seen little application to real-world cases. We discuss relevant research needs and priorities for improved social-ecological impact assessment related to these major physical changes in the climate and oceans. For example, harmonised approaches are needed to better understand impacts from compound events, and cascading impacts across systems. Such information is essential to inform options for adaptation, governance and decision-making. Finally, we highlight research needs for developing transformative adaptation options and their governance.